AI and Cyber-Enabled Threats to Democracy through Algorithmic Manipulation and Generative AI in Undermining Democratic Integrity - Mansur, Md. Abul (European Scientific Journal, ESJ, 2025)
The increasing integration of artificial intelligence (AI) into digital platforms has escalated threats to democratic integrity worldwide, primarily through algorithmic manipulation, generative AI technologies, and large language models (LLMs). This study comprehensively investigates how these advanced technologies are systematically leveraged by state and non-state actors to destabilise democracies. The paper scrutinises empirical cases from the United States, European Union, India, Türkiye, Argentina, and Taiwan, analysing the operational mechanisms and socio-political implications of AI-driven disinformation. Findings demonstrate how generative AI, deepfake technologies, and sophisticated behavioural targeting exacerbate polarisation, weaken institutional trust, and distort electoral processes. Despite the growing prevalence of such cyber-enabled interference, regulatory and institutional responses remain fragmented and inadequate. Consequently, this research culminates in proposing a robust strategic implementation framework, emphasising platform transparency, regulatory innovation, technological safeguards, and civic resilience measures. This framework provides actionable guidance for safeguarding democratic integrity amid evolving AI threats.